Numerical simulation and wind tunnel measurements of lateral aerodynamic characteristics on simplified automotive model - Abd. Rahman, Muhammad Riza (2010)
Computational Fluid Dynamic (CFD) has become an important tool to solve various engineering problems related to aerodynamics. One such growing interest in CFD is to correlate results between CFD and wind tunnel tests. The accuracy of CFD has improved considerably over the years but still large errors are present and lateral aerodynamic characteristics such as drag, side force and yaw moment due to yaw angle are often poorly predicted especially on bluff body shapes. Due to this, comparison between CFD and wind tunnel measurements has become more on demand. The main goal of this research is to investigate the capability of CFD to determine aerodynamic characteristics of simple automotive type bodies and its effect on crosswind stability. An investigation was performed both experimentally and computationally to analyze the main characteristics of flow past a 1:6 scale wind tunnel model of a simplified automotive body shape with different rear slant angles. The investigations were focused on the prediction and measurement of drag, side force, yawing moment and flow characteristics around the model in Reynolds number range of 1.29x10⁶ to 2.14x10⁶ at various yaw angles. The wind tunnel measurements were performed to provide aerodynamic data on vehicle stability and also to build a database for validating the numerical simulation model. The CFD solver FLUENT 6.3 was used to simulate incompressible three dimensional flow with the standard k-£ turbulent models. The result of the wind tunnel tests and the numerical simulations were found to be in good agreement. The results show that the rear slant angles have significant effect on aerodynamics lateral derivatives.